The COVID-19 crisis and the South African informal economy: A stalled recovery - Michael Rogan; Caroline Skinner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper seeks to identify the differentiated impacts of the crisis on specific groups of informal workers. The analysis draws on official nationally representative labour force surveys collected quarterly by South Africa's national statistical agency (Statistics South Africa). Based on an analysis of six quarters of labour market data (with the first quarter of 2020 as the 'pre-COVID' baseline), the paper aims to identify the labour market impacts of the first three waves of the pandemic and of one of the world's strictest 'lockdowns' (as it was described at the time-in April 2020). In investigating the contours of the pandemic's impact on the South African informal economy, the paper focuses, in particular, on the different impacts by gender, sector, and status in employment. The findings show that both relative and absolute job losses have been greater in the informal economy, while the rate and level of recovery have been greater for formal employment. Further, the data suggest uneven impacts within the informal economy with women informal workers, those working in the informal sector and those in retail and community and social services being particularly hard hit. The pandemic period has thus widened pre-existing inequalities and fault lines. In policy terms, this suggests that the informal economy should be a priority in economic recovery efforts but also that support requires differentiated approaches and a range of measures.
Keywords: E24; E26; J21; J46; 330; COVID-19; South Africa; informal economy; labour markets